Pergulatan Identitas Tionghoa Muslim: Pengalaman Yogyakarta - Maulana, Rezza (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2011)
This paper throws light on the historical development of Tionghoa Muslim in Yogyakarta. Using histrorical analysis, it found that the origins of Tionghoa Muslim can be traced back to the early 18th century of Javanese kingdom when, for instance, Sultan Hamengku Buwono III appointed a Muslim of Tionghoa origin to be his regent. In the new order era, Tionghoa Muslim in Yogyakarta kept their low profile against the backdrop of New Order regimeâs policy of assimilation. However, after the gate of democratisation was opened in the late 1990âs, Tionghoa Muslims in this area have enjoyed a freedom to express their identity by, among others, celebrating Chinese New Yearâs festival in the public. The articel then concludes that the construction of Tionghoa Muslimâs identity in Yogyakarta is very much affected by the government policy (politics).